The Relationship Between Nurse’s Professional Quality of Life, Mindfulness, and Hardiness: A Cross-Sectional Study During the COVID-19 Outbreak - Zakeri, Mohammad Ali; Ghaedi-Heidari, Fatemeh; Khaloobagheri, Elham; Hossini Rafsanjanipoor, Sayed Mortaza; Ganjeh, Hamid; Pakdaman, Hassan; Abbasifard, Mitra; Mehdizadeh, Mehdi; Zakeri Bazmandeh, Abbas; Dehghan, Mahlagha (Frontiers in Psychology, 2022)
Background In the pandemic of Coronavirus Disease 2019 (COVID-19) disease, various factors, such as workplace factors, and psychological variables, can affect the occupational status of nurses. This study aimed to assess the relationship between nurses’ professional quality of life, mindfulness, and hardiness during the outbreak of COVID-19. Methods This cross-sectional study included 239 nurses from two medical centers in Rafsanjan, Iran. Quota sampling was performed from August to November 2020. A demographic form, the Professional Quality of Life Scale (ProQOL), the Freiburg Mindfulness Questionnaire-Short Form (FMI-SF), and the Occupational Hardiness Questionnaire (OHQ) were used to collect data. Results The mean age of the participants was 33.20 ± 6.85 years. The majority of the participants were female, married, and employed. Compassion Satisfaction (CS), Secondary Traumatic Stress (STS), and Burnout (BO) were all moderate among nurses. Hardiness was the best predictor of compassion satisfaction. Mindfulness was the best predictor of both secondary traumatic stress and burnout. Psychological hardiness and mindfulness had the greatest impact on nurses’ quality of professional life during the COVID-19 pandemic. Conclusion Caring for COVID-19 patients may lead to BO, CF, and STS; identifying predictors of these can inform the development of interventions to mitigate or minimize BO, CF, and STS in nurses caring for these patients. Furthermore, in order to improve nurses’ quality of professional life, psychological hardiness, and mindfulness, necessary psychological programs and interventions should be designed and implemented.